A new species of hylodes (Anura, Hylodidae) and its secretive underwater breeding behavior - Sa, Fabio P. de [UNESP]; Canedo, Clarissa; Lyra, Mariana L. [UNESP]; Haddad, Celio F. B. [UNESP] (Herpetologists League, 2015)
We describe a new species of Hylodes from the Atlantic forest of Serra do Japi, Municipio de Jundiai, State of Sao Paulo, Brazil. The new species belongs to the Hylodes lateristrigatus group, characterized by light oblique lateral stripes. It is diagnosed by small size; thumbs without nuptial excrescences; relatively smooth dorsal surfaces; interocular area with evident dark blotches of variable shapes (less commonly, exhibiting a uniform pattern or an interocular dark bar); dorsum with large evident dark blotches of variable shapes (less commonly, having a uniform pattern); a mainly light-colored venter; in adult males, paired lateral vocal sacs, widely expanded. The new species is morphologically similar to H. amnicola, H. ornatus, H. perere, and H. sazimai, distinguishable via differences in color pattern and advertisement call. We also analyzed molecular data (partial sequences of two mitochondrial genes and one nuclear gene; COI, 16S, and RAG1, respectively) and found that the new species is genetically distinct from the aforementioned species. We also describe this new species'tadpoles and provide information on its reproductive mode, natural history, and conservation status. We provide details of the new species'secretive underwater breeding that are superficially known for the genus Hylodes, such as spawning, egg traits, and female role in concealing the underwater chamber after oviposition.
Keywords: Atlantic forest; Eggs; Hylodes cf. ornatus; Reproductive mode; Spawning; Tadpole; Vocalization